Utilization of hazardous waste of black dross aluminum: processing and application-a review - Maya Lukita; Zaenal Abidin; Etty Riani; Ahyar Ismail (Brawijaya University, 2022)
Aluminum black dross is produced by the secondary smelting process of aluminum. Aluminum black dross is classified as hazardous waste because it is reactive with water and produces substances and gases that are harmful to humans and the environment. Generally, aluminum black dross is managed by landfill method, but because it is produced in large amounts every year, the aluminum black dross needs to be utilized to reduce the impact on the environment. Aluminum black dross consists of large amounts of metal oxide and salts. The amount of metal oxide content in aluminum black dross can be used as raw material. This paper review types of processes for utilizing black dross aluminum as raw material in value-added products. aluminum black dross can be used as alumina, adsorbent, zeolite, composites, geopolymers, refractories, and fillers. By utilizing aluminum black dross waste into various products that have economic value, besides being able to protect the environment, it can also reduce environmental resource use.